Ambidextrous leadership and innovative work behavior: the roles of self-efficacy, resilience, and organizational support - Kusumah, Adie Irwan; Setiawan, Iwan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to analyze the effect of ambidextrous leadership on innovative work behavior by considering the mediating role of innovative self-efficacy as well as the moderating effect of psychological resilience and perceived organizational support. This study was conducted in the manufacturing and service sectors in the West Java region involving 480 respondents working in 134 companies. Data were collected through a questionnaire survey and analyzed using the Structural Equation Modeling (SEM) approach with the help of SmartPLS software. The results showed that ambidextrous leadership has a positive and significant effect on innovative work behavior. Innovative self-efficacy was shown to play a mediating role in the relationship, which means that an individual's belief in his or her ability to innovate strengthens the impact of ambidextrous leadership style on innovative behavior. In addition, psychological resilience moderated the relationship between ambidextrous leadership and innovative self-efficacy, while perceived organizational support moderated the relationship between innovative self-efficacy and innovative work behavior. Both moderator variables strengthen the relationship between variables when they are at high levels. The findings provide theoretical and practical implications, especially for organizations that want to build an innovative culture through strengthening leadership capacity and psychological factors and support perceived by employees. By creating a work environment that supports idea exploration and self-development, organizations can sustainably increase innovative work behavior.